Pengembangan Game Edukasi Baamboozle Berbasis Assure Untuk Pendidikan Agama Islam - Fadllah Utami; Mardiah Astuti; Gatot Kaca (PAI RAFAH, 2025)
The ASSURE learning model provides a structured framework for designing effective instruction by integrating suitable media, methods, and materials. This study aims to develop a Baamboozle-based educational game grounded in the ASSURE model for Grade 5 Islamic Religious Education (PAI). The objectives are to assess the game's impact on student engagement, gather feedback from students and teachers, and explore the practical use of the ASSURE model in educational game development. Using a qualitative descriptive approach with a case study design, data were collected through observations, interviews, and documentation, and analyzed through data reduction, display, conclusion drawing, and verification. Results show that the Baamboozle game enhances student interaction with PAI materials. The structured use of the ASSURE model assists teachers in creating engaging, student-centered learning. Additionally, the game's interactive features improve participation, motivation, and understanding, fostering an effective and dynamic learning environment.